Application of Light-Responsive Nanomaterials in Bone Tissue Engineering - Aiguo Liu; Chenxu Wang; Shuang Deng; Sitong Zhang; Ziwen Zhao; Han Xiao; Ting Ying; Chengqing Yi; Dejian Li (Pharmaceutics)
The application of light-responsive nanomaterials (LRNs) in bone tissue engineering shows broad prospects, especially in promoting bone healing and regeneration. With a deeper understanding of the mechanisms of bone defects and healing disorders, LRNs are receiving increasing attention due to their non-invasive, controllable, and efficient properties. These materials can regulate cellular biological reactions and promote bone cell adhesion, proliferation, and differentiation by absorbing specific wavelengths of light and converting them into physical and chemical signals. In addition, the unique surface morphology and biocompatibility of LRNs enable them to effectively load drugs in bone tissue engineering, achieve precise release, and optimize the bone regeneration process. Through photothermal and photodynamic therapy, these materials also possess antibacterial properties and can play an important role in the repair of infectious bone defects. Although LRNs have shown significant advantages in bone tissue regeneration, a series of challenges still need to be overcome to achieve their widespread and effective clinical applications. This article summarizes the basic principles, classification, and potential applications of LRNs in bone tissue regeneration, aiming to provide reference for future research and clinical applications.